Undang-Undang Cipta Kerja Dan Dampaknya Terhadap Ekonomi Mikro - Sriayu Aritha Panggabean; Amaludin Sikumbang (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
Based on the rules and unhealthy relationships due to legislation written in the labor law in force in Indonesia, it underlies the government to create a new law which eventually creates the omnibus law with the aim of reducing the unemployment rate in Indonesia. Indonesia has the concept of a state based on law (rechtsstaat) which includes issues from human rights to clear law and of course based on law. Building the economy is a very important thing to build to achieve people's welfare. The results of this study are: the new law that was created, namely the omnibus law, in the process of implementing it, many conflicts occurred. This problem is seen from the problems that arise simultaneously. The omnibus law has also been implemented in several regions and legal regulations in Indonesia. all laws that have been made, must have an impact with legal certainty with the subject and object of the rule. With the creation of this new law, many positive changes have been seen in the economy where it is easy for business actors to obtain business licenses, mapping the risk level of business licenses, how to arrange business licenses, NIB as a requirement in the halal certificate process, establishment of PT Individuals, access to banking, assistance and legal protection, as well as financial training which was not found in the previous law